Histologist NK Kulchytsky: scientific and socio-political activities (To the 160th anniversary of his birth). - Protsenko, E. S.; Padalko, V. I.; Remneva, N. A.; Kirichenko, M. I. (Морфологія / Morphologia / Morfologìâ, 2016)
The article presents the biographic data about professor K. N. Kulchitsky. It concerns his scientific and practical contribution to the development of histological investigations in Kharkov Imperial University and in London University College. Consideration is also being given to the social and political activity of the scientist, including as Minister of Education for all of Russia Imperia.